Student perceptions of the use of scaffolding method in reading class - Rahmatun Nisa; Siti Safura; Nita Kasmita (ACCENTIA: Journal of English Language and Education, 2020)
This study explored the student perceptions of scaffolding method used in teaching reading. The study took place at a vocational senior high school in Banda Aceh, Aceh, Indonesia. The study used descriptive quantitative research method, gathering data from questionnaires. The study took 10 students as the respondents. The results showed that most students felt the scaffolding method made them easily understand the stories in the reading class, and thus they became more motivated to read. The authors expect that this method can be used in many English reading classes in Indonesia.